"Anonymous Meltdown": Content Themes Emerging in a Nonfacilitated, Peer-only, Unstructured, Asynchronous Online Support Group for Family Caregivers. Issue 12 (December 2017) - Diefenbeck, Cynthia A.; Klemm, Paula R.; Hayes, Evelyn R.
Abstract : By providing care for loved ones in the home, family caregivers save millions of dollars for our overtaxed healthcare system. Support groups can lighten the psychological burden of caregiving. Nonprofessionally facilitated (or peer) online caregiver support groups can help meet a critical need in healthcare as a low-cost resource for caregivers. Online caregiver peer support groups can promote the health and well-being of family caregivers and, by extension, the patients themselves, resulting in cost-savings for society. A better understanding of these types of groups is of critical importance, given the unrelenting pace of demographic shift in the United States. The purpose of this study was to examine content themes emerging from an unstructured, asynchronous online peer support group for family caregivers of people with chronic illness. Qualitative content analysis was used, yielding six themes: "experiencing the emotional toll, " "need for catharsis/venting, " "finding the silver linings, " "seeking specific advice/problem solving, " "realizing home is no longer a haven, " and "adapting to the caregiver role." The themes reflect what emerged organically in an online support group that was not professionally facilitated or structured in any way. Heterogeneity in the relationship between caregivers and care recipients may negatively affect outcomes and requires further study.